P125 Engaging pregnant women in a dance-based exercise class: A focus group study of women's views and experiences. (13th September 2016) - Smith, LA; Adams, E; Burns, E
Abstract : Background: Women can feel socially isolated when pregnant for the first time, and may become anxious about pregnancy, childbirth and the transition to parenthood. The UK national maternal satisfaction survey indicates that lack of continuity of care and continuity of carer during antenatal period is a common complaint. Furthermore, access to state supported antenatal parenting classes has been much reduced over recent years. The Royal College of Obstetrics and Gynaecology (RCOG) state that recreational exercise during pregnancy improves muscle tone, strength and endurance, makes it easier to carry the additional weight of pregnancy and helps women prepare for the physical challenges of labour and delivery. Nevertheless, current recommendations are not reflected by reported activity levels in recent studies in high-income countries with a trend for physical activity levels to decline further as pregnancy progresses. We have developed 'Club BUMP' a community-based dance class and social group where pregnant women or women who have recently given birth receive health and lifestyle-related advice and support from a midwife and emotional and practical support from each other. The aim of this study was to explore women's views and experience of attending Club Bump. The objectives were to identify factors that facilitated or hindered initial attendance, and factors that facilitated or hindered sustained attendance. Methods: A qualitative research design with a social marketing approach was used to address these objectives. Five focus groups were conducted which ranged between three and eight women with a healthy pregnancy and no contraindications to exercise who had attended Club Bump for one or more sessions between March 2013 and November 2014. Audio-recorded data were transcribed verbatim, and analysed using framework analysis using NVivo 9. Results: The deductive analytic process produced information about the preferred positioning of the class in relation to the predefined social marketing dimensions for services of product, place, price, promotion, person, physical evidence and process (7 Ps) across the entire dataset. One important finding was that a main aspect of its appeal was that the class felt fun, achievable and safe which helped decrease anxiety about potential risks of harm from exercise. Peer group support was also an important aspect which fostered a sense of belonging to a group. Further findings in relation to the 7 Ps will be presented. Conclusion: The social marketing model is a useful framework to help identify the elements that are important to take into consideration when developing a new community-based complex intervention that aims to engage pregnant women in an exercise class.